Early Morphokinetic Monitoring of Embryos after Intracytoplasmic Sperm Injection with Fresh Ejaculate Sperm in Nonmosaic Klinefelter Syndrome: A Different Presentation - Ali Sami Gurbuz; Ahmet Salvarci; Necati Ozcimen; Ayse Gul Zamani (Case Reports in Genetics, 2015)
The patient was diagnosed with nonmosaic 47, XXY Klinefelter Syndrome with the AZF deletion absent and SRY+. The nonmosaic 47, XXY karyotype was confirmed on a skin biopsy chromosomal analysis. Using only ejaculate motile sperms, 11 oocytes underwent ICSI and were placed rapidly in a time lapse (Embryoscope ©) with a specific culture dish. Biopsies were performed on six embryos on the 3rd day, and numerical chromosomal abnormalities were observed using the FISH test before transfer. PGS results were normal in only two embryos with normal morphokinetics in the Embryoscope. For clinical confirmation of pregnancy, ultrasonographic examination was performed during the 7th week of pregnancy, and two gestational sacs and fetal heart beat were observed.